Inflammation pathways as therapeutic targets in angiotensin II induced atrial fibrillation - Hou, Ailin; Shi, Dazhuo; Huang, Hongbo; Liu, Yuxuan; Zhang, Ying (Frontiers in Pharmacology, 2025)
Atrial fibrillation (AF), a common cardiac arrhythmia, is associated with severe complications such as stroke and heart failure. Although the precise mechanisms underlying AF remain elusive, inflammation is acknowledged as a pivotal factor in its progression. Angiotensin II (AngII) is implicated in promoting atrial remodeling and inflammation. However, the exact pathways through which AngII exacerbates AF are still not fully defined. This study explores the key molecular mechanisms involved, including dysregulation of calcium ions, altered connexin expression, and activation of signaling pathways such as TGF-β, PI3K/AKT, MAPK, NF-κB/NLRP3, and Rac1/JAK/STAT3. These pathways are instrumental in contributing to atrial fibrosis, electrical remodeling, and increased susceptibility to AF. Ang II-induced inflammation disrupts ion channel function, resulting in structural and electrical remodeling of the atria and significantly elevating the risk of AF. Anti-inflammatory treatments such as RAAS inhibitors, colchicine, and statins have demonstrated potential in reducing the incidence of AF, although clinical outcomes are inconsistent. This manuscript underscores the link between AngII-induced inflammation and the development of AF, proposing the importance of targeting inflammation in the management of AF.